Pengaruh Likuiditas, Leverage dan Profitabilitas terhadap Financial Distress pada PT. Modern Internasional Tbk - Yani, Vita; Putri Gami, Emelia Rahmadany (All Fields of Science Journal Liaison Academia and Sosiety, 2022)
The purpose of this study is to find out whether there is a Liquidity Effect, Leverage and profitability to Financial Distress at PT Modern International, Tbk, partially and simultaneously. The sample of this study is the financial statements of PT.Modern Internasional Tbk, which are listed on the Indonesia Stock Exchange financial statements used for this study are financial statements from 2012 to 2017, Data analysis using Multiple Linear Regression test, hypothesis testing using the coefficient of determination test (R2), partial test (T Test) and simultaneous test (F Test), while the data processor uses the SPSS 20 program. The results show that from the test of the coefficient of determination (R2) the liquidity variable is Current Ratio (CR), Leverage namely Debt to Asset Ratio (DAR), and profitability, namely return on assets (ROA) and return on equity (ROE) can explain the variations that occur in financial distress of PT. Modern International, Tbk. Partially (T Test) current assets (CR), debt to assets ratio (DAR), return on assets (ROA) and Return of Equity (ROE) have no effect and are not significant to financial distress. Simultaneously (Test F) current ratio (CR), debt to asset ratio (DAR), return of assets (ROA) and return of equity (ROE) influence and are not significant to financial distress at PT.Modern Internasional, Tbk Keywords: Liquidity (CR), Leverage (DAR), Profitability (ROA & ROE), Financial Distress.